2021
DOI: 10.1177/17562864211042458
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for loss of natalizumab effectiveness with every-6-week dosing: a propensity score–matched comparison with every-4-week dosing in patients enrolled in the Tysabri Observational Program (TOP)

Abstract: Background: Extended interval dosing of natalizumab is associated with significantly lower progressive multifocal leukoencephalopathy risk compared with every-4-week (Q4W) dosing in patients with relapsing-remitting multiple sclerosis. Previous studies have suggested that natalizumab effectiveness is maintained in patients who switch from Q4W to extended interval dosing but have been limited by a lack of well-matched patient cohorts. Methods: Tysabri Observational Program (TOP) data as of November 2019 were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…TOP participants on EID and SID dosing had similar incidence of all serious adverse events (SAEs) as well as SAEs related to treatment based on a qualitative assessment. Two cases of PML were observed in this study, both in the EID dosing group; notably, both PML cases were characterized by the presence of known risk factors for PML and were, therefore, in the highest PML risk category (Butzkueven et al, 2021a). The study showed that natalizumab effectiveness is maintained in those PwMS who switch to EID after ≥1 year on SID treatment regimen (Butzkueven et al, 2021a).…”
Section: Long-term Efficacy and Safety Of Natalizumabmentioning
confidence: 58%
See 2 more Smart Citations
“…TOP participants on EID and SID dosing had similar incidence of all serious adverse events (SAEs) as well as SAEs related to treatment based on a qualitative assessment. Two cases of PML were observed in this study, both in the EID dosing group; notably, both PML cases were characterized by the presence of known risk factors for PML and were, therefore, in the highest PML risk category (Butzkueven et al, 2021a). The study showed that natalizumab effectiveness is maintained in those PwMS who switch to EID after ≥1 year on SID treatment regimen (Butzkueven et al, 2021a).…”
Section: Long-term Efficacy and Safety Of Natalizumabmentioning
confidence: 58%
“…The first step in exploring the utility of EID with natalizumab to reduce the risk of PML is establishing that there is no loss of clinical effectiveness. As described earlier, long-term data from the TOP registry indicate that the effectiveness of natalizumab is maintained with an EID schedule in comparison with SID, with no change to the safety profile (Butzkueven et al, 2021a). A number of real-world studies further support the findings that EID maintains the efficacy of natalizumab in cohorts that include anti-JCV antibody-positive and antibody-negative PwMS (Butzkueven et al, 2020a;Chisari et al, 2020;De Mercanti et al, 2021;Riancho et al, 2021).…”
Section: Extended Interval Dosingmentioning
confidence: 58%
See 1 more Smart Citation
“…Today, emerging evidence suggests that extended interval dosing (EID) NTZ (infusion every 6 wk) might decrease the risk of PML among patients who were positive for JCV antibodies and had received prior immunosuppressants compared to standard interval dosing (SID) (every 4 wk) 43 . NTZ effectiveness was maintained when switched to EID from SID after more than 1‐y treatment 44 . However, it should be noted that the risk of PML cannot be completely eliminated with EID, and vigilance is required even under this regimen 45 …”
Section: Viral Infectionsmentioning
confidence: 99%
“…43 NTZ effectiveness was maintained when switched to EID from SID after more than 1-y treatment. 44 However, it should be noted that the risk of PML cannot be completely eliminated with EID, and vigilance is required even under this regimen. 45 Compared to NTZ, the risk of PML was lower with other mAbs.…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 99%